SAE Technical Paper Series 2020
DOI: 10.4271/2020-01-2012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Scavenging Process in a Large Two-Stroke Marine Engine Using URANS and LES Turbulence Models

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Nemati et al applied URANS and LES on the scavenging process of a large 2-stroke diesel engine and compared their results with PIV data. Although they found a good agreement with the measurements for both solutions, too, they stated a better prediction of the tangential velocity for LES [16]. Very similar results were found for an uniflow-scavenged cylinder in [17] and for an optical engine in [18].…”
Section: Basic Challenges Of Turbulent In-cylinder Flowsupporting
confidence: 58%
“…Nemati et al applied URANS and LES on the scavenging process of a large 2-stroke diesel engine and compared their results with PIV data. Although they found a good agreement with the measurements for both solutions, too, they stated a better prediction of the tangential velocity for LES [16]. Very similar results were found for an uniflow-scavenged cylinder in [17] and for an optical engine in [18].…”
Section: Basic Challenges Of Turbulent In-cylinder Flowsupporting
confidence: 58%
“…From the turbochargers, the air is led via the charging air pipe, through air coolers and scavenge air receiver to ports of the cylinder liners [31]. The scavenging process is responsible for delivering fresh air to the combustion chamber and removing combustion gases in the cylinder [32]. The scavenging process affects the air pollution and its operation is strictly controlled and regulated [33]; it improves the combustion efficiency due to a better air/gas exchange [34].…”
Section: Ati-2023mentioning
confidence: 99%
“…Through 1D model simulations on a diesel engine with a cylinder bore of 500 mm, the results indicated that this technology can improve the thermal efficiency, reduce the fuel consumption by 4.3 g/(kW•h), and benefit the design and cost-efficiency of SCR systems. Computational Fluid Dynamics (CFD) has been extensively employed to analyze the scavenging and combustion processes of low-speed two-stroke diesel engines [24][25][26][27]. However, few literature works have utilized the CFD method to assess the effects of the VPT technology on the operational procedures of marine low-speed two-stroke engines.…”
Section: Model Description and Validationmentioning
confidence: 99%
“…Computational Fluid Dynamics (CFD) has been extensively employed to analyze the scavenging and combustion processes of low-speed two-stroke diesel engines [24][25][26][27]. However, few literature works have utilized the CFD method to assess the effects of the VPT technology on the operational procedures of marine low-speed two-stroke engines.…”
Section: Introductionmentioning
confidence: 99%